2019
DOI: 10.1182/bloodadvances.2018028795
|View full text |Cite
|
Sign up to set email alerts
|

Predisposition to childhood acute lymphoblastic leukemia caused by a constitutional translocation disrupting ETV6

Abstract: Key PointsWe report the first known family with a constitutional translocation disrupting ETV6 predisposing to ALL. Germline monoallelic expression of ETV6 contributes to leukemia predisposition without thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
(93 reference statements)
0
8
0
2
Order By: Relevance
“…[13][14][15] Additional studies have recently identified familial leukemia cases with inherited structural alterations in the ETV6 gene, further highlighting the role of this gene in ALL predisposition. 16,17 To explore the contribution of germline variation in ETV6 more broadly in childhood ALL, we subsequently sequenced 4405 childhood B-ALL cases and identified potential leukemia-related variants in ;1% of patients. 18 Of these, nearly half were located in the essential DNA-binding domain, including 9 variants predicted to be most deleterious by the combined annotationdependent depletion scores.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Additional studies have recently identified familial leukemia cases with inherited structural alterations in the ETV6 gene, further highlighting the role of this gene in ALL predisposition. 16,17 To explore the contribution of germline variation in ETV6 more broadly in childhood ALL, we subsequently sequenced 4405 childhood B-ALL cases and identified potential leukemia-related variants in ;1% of patients. 18 Of these, nearly half were located in the essential DNA-binding domain, including 9 variants predicted to be most deleterious by the combined annotationdependent depletion scores.…”
Section: Introductionmentioning
confidence: 99%
“…CNV analysis revealed that a significant proportion of PID-related genes were altered across the four pediatric cancer cohorts examined. Deep deletion of ETV6 , a transcription-regulating gene, has been previously implicated in leukemias and may play a role in oncogenesis, treatment response, and outcome in pediatric ALL patients [ 44 , 45 , 46 , 47 ]. Furthermore, the analysis identified CNVs in the ribosomal protein (RP) gene family, specifically RPS15 , with relation to deep deletion in pediatric ALL and AML.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a focal germline ETV6 splice site deletion resulting in exon skipping and protein truncation has been reported in a highly penetrant family (Rampersaud et al 2019). Another report identified a constitutional translocation disrupting ETV6 (Jarviaho et al 2019). These studies indicate that careful analysis of germline structural variants is required to describe the full repertoire of deleterious germline alterations in ALL.…”
Section: Inherited Variants In Allmentioning
confidence: 98%